Residual urinary extracellular vesicles in ultracentrifugation supernatants after hydrostatic filtration dialysis enrichment. Issue 1 (1st December 2017) - Musante, Luca; Tataruch‐Weinert, Dorota; Kerjaschki, Dontscho; Henry, Michael; Meleady, Paula; Holthofer, Harry
ABSTRACT: Urinary extracellular vesicles (UEVs) appear an ideal source of biomarkers for kidney and urogenital diseases. The majority of protocols designed for their isolation are based on differential centrifugation steps. However, little is still known of the type and amount of vesicles left in the supernatant. Here we used an isolation protocol for UEVs which uses hydrostatic filtration dialysis as first pre‐enrichment step, followed by differential centrifugation. Transmission electron microscopy (TEM), mass spectrometry (MS), western blot, ELISA assays and tuneable resistive pulse sensing (TRPS) were used to characterise and quantify UEVs in the ultracentrifugation supernatant. TEM showed the presence of a variety of small size vesicles in the supernatant while protein identification by MS matched accurately with the protein list available in Vesiclepedia. Screening and relative quantification for specific vesicle markers showed that the supernatant was preferentially positive for CD9 and TSG101. ELISA tests for quantification of exosome revealed that 14%, was left in the supernatant with a particle diameter of 110 nm and concentration of 1.54 × 10 10 /ml. Here we show a comprehensive characterisation of exosomes and other small size urinary vesicles which the conventional differential centrifugation protocol may lose.